The Effect of Anadara granosa Shell’s–Stichopus hermanni Scaffold on CD44 and IL-10 Expression to Decrease Osteoclasts in Socket Healing - Sari, Rima Parwati; Revianti, Syamsulina; Andriani, Dwi; Prananingrum, Widyasri; Rahayu, Retno Pudji; Sudjarwo, Sri Agus (European Journal of Dentistry, 2021)
Objectives This article aimed to investigate the effect of Anadara granosa (AG) shell’s–Stichopus hermanni scaffold on cluster of differentiation (CD)44 and interleukin-10 (IL-10) expression to decrease osteoclasts in socket healing.Materials and Methods Thirty male Wistar rats were divided into five groups. The lower left incisor was extracted, then given a placebo for group control (K), the treatment group was administered with scaffold from AG shells, and a treatment group with scaffold from blood cockle shell–S. hermanni with the concentration of 0.4, 0.8, and 1.6% (AGSH0.4; AGSH0.8; AGSH1.6). We made a bone graft from a combination of AGSH extract using the freeze-dried method. The socket was sutured by silk braid immediately. Third and Seventh days postextraction, animals are killed. CD44 and IL-10 expression were examined with immunohistochemistry, as well as osteoclast was examined with hematoxylin-eosin.Statistical Analysis The data were analyzed using a one-way analysis of variance (for CD44 and osteoclast) and Kruskal–Wallis’ test (for IL-10) followed by a post hoc test in which the result of p < 0.05.Results Scaffold from a combination of AGSH increased CD44 expression significantly, which enhanced IL-10 expression thereby decreased the number of osteoclasts in socket healing on days 3 and 7.Conclusion Scaffold of AG shell–S. hermanni with a concentration of 0.8% was effective to enhance CD44 and IL-10 expression to decrease osteoclast in socket healing after tooth extraction.
Keywords: Anadara granosa shell; Stichopus hermanni; hyaluronic acid; CD44; IL-10; osteoclast; socket healing